2011
DOI: 10.1227/neu.0b013e31820b4f1c
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Digital Subtraction Angiography Systems Within the Hybrid Operating Room

Abstract: This newly developed robotic DSA system provides safe and precise treatment in the fields of endovascular treatment and neurosurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 7 publications
0
37
0
Order By: Relevance
“…In a hybrid operative suite containing a fixed C-arm, FDCT can be directly used for frameless neuronavigation because the patient's head is fixed in space throughout the procedure. 6,8,13 Hybrid operative suites, however, require considerable technical and engineering resources, which can be costly. The 3D DSA images have been fused and coregistered with CT or MRI scans for neuronavigation during surgery for complex aneurysms and AVMs.…”
Section: Discussionmentioning
confidence: 99%
“…In a hybrid operative suite containing a fixed C-arm, FDCT can be directly used for frameless neuronavigation because the patient's head is fixed in space throughout the procedure. 6,8,13 Hybrid operative suites, however, require considerable technical and engineering resources, which can be costly. The 3D DSA images have been fused and coregistered with CT or MRI scans for neuronavigation during surgery for complex aneurysms and AVMs.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve a safe and effective endovascular and surgical environment, we have established a new concept: the hybrid endovascular OR for the treatment of neurovascular diseases 9 10. Becoming more popular in modern neurosurgery, this type of hybrid OR accommodates the innovations of conventional neurosurgery with those of the widely used minimally invasive endovascular neurosurgery.…”
Section: Introductionmentioning
confidence: 99%
“…Murayama and Irie et al [4] recently reported further developments on their DynaCT based intra-operative imaging suite. They incorporated a robotic multiaxis C-arm for DSA to a surgical operating room table.…”
Section: Discussionmentioning
confidence: 99%